The art of less : how to focus on what really matters at work - Alvesson, Mats, 1956- (Bloomsbury Business, 2025)
At work we often feel weighed down by an excess of initiatives, meetings, training and targets. Over-enthusiastic executives, interfering consultants and demanding stakeholders often get in the way of doing the 'real work'. This leaves us feeling overwhelmed but underproductive. The Art of Less offers ideas for how to create a more effective and efficient organization by removing obstacles to meaningful work. Mats Alvesson and André Spicer explain how 'organizational sludge' gets in the way of performance, and what can be done about it. They show how unblocking systems and processes can improve work flow so people can focus more on the things that actually matter.